Qualitative data regarding the experiences of pregnant women with lupus in Brazil - Rodrigues, Larissa (2021)
A qualitative design was performed as individual face-toface interviews with each participant, following a semistructured script based on open questions. Participants were interviewed at a specialized clinic, where, during prenatal care, women with stable systemic lupus erythematosus disease were received scheduled consultations. The sample was intentionally composed of women who attended a specialized high-risk clinic, from July 2017 to July 2018. Participants (N = 26) were interviewed in-depth, without refusal. A thematic analysis, according to the 7 steps of the qualitative analysis, was performed. Before conducting interviews, the researcher went through a period of environmental adaptation to the clinic, following a service observation script and maturing the open consultation script questions, to deepen the themes derived from these women’s perceptions during the individual interview. Two authors analyzed the material, which was recorded as audio and transcribed in full; later, the material that was organized in the NVIVO 11 software was validated